AROK’S LEADERSHIP FROM THE ASTHABRATA PERSPECTIVE IN AROK DEDES NOVEL BY PRAMOEDYA ANANTA TOER - I Wayan Nitayadnya (Pusbindiklat - LIPI, 2013)
The concept of leadership is not only useful for the leader but it is also useful for everyone who is led, meaning that by understanding the concept of good leadership, a leader will be able to do what he should do and how the follower should shows their loyalty and dedication to the leader. By using the leadership role contained in the Arok Dedes novel written by Pramoedya Ananta Toer, the objectives to be achieved in this study were (1) reveals patterns how Arok leads, (2) reveals leadership perspective of Asthabrata Arok, and (3) knowing the relevance Arok leadership in relation to the present leadership and the future leadership. The method used in the data collection is the literature study. The data analysis is carried out by reconstruction and reflection text (text meaning), then proceed with interpretation by evaluating the perspective of Asthabrata leadership and correlate the text with the concept of leadership in the future leadership. The result of the analysis shows that the leadership pattern of Arok reflects strong leadership and fairness. Arok leadership represents the leadership of Asthabrata. The character of leadership is very relevant to be applied in order to leading a nation in which experiencing a crisis of leadership like today.